A nested case-control analysis of factors influencing preoperative hospitalization fear in pediatric patients and the alleviating effects of child-friendly visual interventions - Liuxia Bian; Tingting Zhang; Yushan Wu; Xiaomin Shan (BMC Pediatrics)
Abstract Background Preoperative fear in pediatric patients can significantly impact their psychological well-being and complicate perioperative care. Traditional hospital environments may exacerbate anxiety in children undergoing elective surgeries, especially given developmental differences across ages 2 to 12. Methods In a retrospective hospital-based nested case-control study embedded within a cohort, we examined 188 children aged 2 to 12 admitted for elective surgery between March 2023 and March 2024. Participants met specific inclusion criteria and We defined cases as those with a Child Medical Fear Scale (CMFS) score > 30 (High Fear Group) and controls as those with CMFS ≤ 30 (Low Fear Group). Further stratification was based on hospitalization in conventional wards a conventional environment versus specially designed wards featuring “child-friendly visual intervention strategies” (e.g., cartoon themes, interactive toys, multimedia TVs). Standard Routine pre-hospital care (Treatment as Usual) and detailed procedural explanations were provided. Fear Preoperative fear was assessed using the CMFS at admission and before surgery, while parental satisfaction was evaluated with the Patient Satisfaction Questionnaire Short Form (PSQ-18). Results Among 188 children (mean age 7.57 ± 2.15 years; 64/124 male), 74 cases (high fear) and 71 controls (low fear) were analyzed. No significant demographic differences were observed between groups. Key correlates of higher fear included lower educational status (OR = 0.400, 95% CI = 0.200-0.801; P = 0.010) and higher ASA status (OR = 2.273, 95% CI = 1.035–4.989; P = 0.041). Environmental stressors such as visibility of sharp instruments (OR = 2.294, 95% CI = 1.048–5.021; P = 0.038) and observing injections (OR = 2.565, 95% CI = 1.183–5.557; P = 0.017) were significant anxiety factors. The child-friendly intervention group (n = 43) exhibited significantly lower fear scores across all dimensions compared to the conventional group (n = 35), with a higher proportion achieving CMFS ≤ 30 (76.74% vs. 51.43%; P = 0.019) and greater parental satisfaction (79.07% vs. 51.43%; P = 0.010). Conclusion Both individual (e.g., educational status, past hospital experiences) and environmental factors (e.g., visibility of needles) play critical roles in pediatric preoperative fear. Implementing child-friendly visual interventions significantly alleviates reduces anxiety and improves parental satisfaction. These findings Our results support the adoption of such strategies in pediatric surgical care and highlight the importance of age-appropriate interventions.